Challenges and potentials of developing domperidone into the transdermal delivery - Sekar Ayu Pawestri; Akhmad Kharis Nugroho; Endang Lukitaningsih; Purwantiningsih Purwantiningsih (Majalah Farmaseutik, 2022)
Nausea, which often coexists with vomiting, is an uneasy sensation in the stomach caused by several factors. Oral domperidone is widely prescribed in nausea treatment. The low bioavailability of oral domperidone makes a patient take the drug more frequently, even though some patients have difficulty swallowing the drug when suffering nausea. Recently, the drug formulation development for transdermal delivery systems is expected to increase in the future. Practical and increase patient comfortable is the notable advantages of using transdermal dosage form. Domperidone is currently being studied into various pharmaceutical dosage forms with the transdermal route. This present article provides summaries of the constraints also the current formulation development of domperidone which shows the potential of domperidone in transdermal delivery.